Analysis Of Portion Standards, Menu Patterns, And Food Acceptability On Levels Of Availability And Consumption Of Energy And Nutritional Substances In Ma'had Tahfizhul Qur'an Al-Firqoh An- Najiyah Food Implementation In Malang District - madani, zafira putri; Hakimah, Nurul; Nurmayanti, Rani (Journal of Local Therapy, 2024)
The background : of this study is that the nutritional needs of adolescents are relatively large, because they are still experiencing growth. In addition, adolescents generally carry out higher levels of physical activity compared to other ages. In addition, female adolescents are an age group that is vulnerable to nutritional problems, especially anemia, so that more nutrients are needed. A balanced menu pattern and portion standards will greatly affect the nutritional value of each dish. The aim of the study : was to analyze portion standards, menu patterns, and food acceptability on the level of availability and consumption levels of energy and nutrients in Ma'had Tahfizhul Qur'an Al-Firqoh An-Najiyah Food Service in Malang Regency. This research method : is a type of research that is descriptive qualitative with a cross-sectional study design, meaning that the observations are made at the same time. The results : of the analysis show that most of the menus served by the organization of Ma'had food are not included in the balanced category. The breakfast as a whole falls into the unbalanced category by (100%), this is because the food organizers only provide a menu of animal side dishes once a day at dinner, and twice a day for vegetable side dishes at breakfast and lunch. The presentation of staple foods, vegetables and fruit is in the category of less than the standard portion, but the types of animal side dishes and vegetable side dishes exceed and almost meet the set portion standards. Acceptability of food shows that respondents do not like the color and texture of the food served by the food organizer, this is due to the repetition of the menu which results in a lack of interest of the respondents in food. inadequate portion standards and budgets. the adequacy of nutrients such as energy, fat, carbohydrates, vitamins C and Fe (iron), is still classified as a severe deficit, this is due to the lack of compliance with the proportions of female students, interest in the food menu, lack of awareness of fulfillment of nutrients, and unhealthy eating patterns Wrong